2021
DOI: 10.1037/pag0000651
|View full text |Cite
|
Sign up to set email alerts
|

A developmental–contextual model of couple synchrony across adulthood and old age.

Abstract: Most theoretical models on social dynamics governing development and health across adulthood and old age rely on a “single-unit” approach. We put forth a developmental–contextual model (CoSynch) that utilizes the concept of synchrony (interdependent fluctuations in physiological states and health behaviors) as a novel way to conceptualize social developmental dynamics. Using the sample case of romantic partners, this model aims for an innovative integration of available findings addressing everyday microsocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 121 publications
(177 reference statements)
3
9
0
Order By: Relevance
“…This reasoning is in line with findings on dyadic coping (e.g., Bodenmann, 2005) and couple synchrony (see Pauly et al, 2021). According to Bodenmann's Systemic-Transactional Model of Dyadic Coping (Bodenmann, 2005), when partners deal with a stressor affecting them both directly and simultaneously, such as in the COVID-19 pandemic, the source of stress is defined as common, and dyadic stress is observed.…”
Section: Intimate Relationships During the Covid-19 Pandemicsupporting
confidence: 90%
See 3 more Smart Citations
“…This reasoning is in line with findings on dyadic coping (e.g., Bodenmann, 2005) and couple synchrony (see Pauly et al, 2021). According to Bodenmann's Systemic-Transactional Model of Dyadic Coping (Bodenmann, 2005), when partners deal with a stressor affecting them both directly and simultaneously, such as in the COVID-19 pandemic, the source of stress is defined as common, and dyadic stress is observed.…”
Section: Intimate Relationships During the Covid-19 Pandemicsupporting
confidence: 90%
“…Our data thus seem to suggest that being faced with the strict short-time lockdown -as an acute stressor-initially brought most couples together, whereas the chronic stress exposure (i.e., one-year pandemic) began to break them apart. This reasoning is in line with findings on dyadic coping (e.g., Bodenmann, 2005) and couple synchrony (see Pauly et al, 2021). According to Bodenmann's Systemic-Transactional Model of Dyadic Coping (Bodenmann, 2005), when partners deal with a stressor affecting them both directly and simultaneously, such as in the COVID-19 pandemic, the source of stress is defined as common, and dyadic stress is observed.…”
Section: Intimate Relationships During the Covid-19 Pandemicsupporting
confidence: 81%
See 2 more Smart Citations
“…Prior research has reported that moments of physical and emotional closeness between partners are associated with greater cortisol synchrony ( Pauly, Gerstorf, et al, 2021 ). Thus, future research could build on these findings by not only investigating whether cortisol levels are lower following moments of intimacy in daily life, but also whether cortisol and affect levels of both partners synchronize after such interactions.…”
Section: Discussionmentioning
confidence: 99%